A concise text-book of organic chemistry - Lyons, C. G. (Charles George); McLintock, S.; Lumb, Nora H. (Commonwealth and international library. Chemistry division., 1965)
A Concise Text-Book of Organic Chemistry presents a concise account of organic chemistry and covers organic compounds ranging from aliphatic hydrocarbons and aliphatic acids to amino and nitro compounds, carbohydrates, and aromatic acids. Flow sheets and tables of comparisons between aliphatic and aromatic compounds are included, and a variety of industrial processes such as synthetic processes are described. This textbook is comprised of 20 chapters and begins with an introduction to the nature of organic chemistry, paying particular attention to the molecular and constitutional formulas of o.